A Spatial Analysis of The Human Environmental Factors Affecting the Increase in Soil Salinity in Al-Qadisiyah - Almudhafar Safaa M.; Hamza Bneen M.; Almayahi Basim A. (E3S Web of Conferences)
The human factor is one of the most important factors that can affect soil salinity , as man plays an important role in influencing and changing it through various agricultural activities such as tillage, levelling, agriculture, irrigation, drainage , fertilization, and the whole of these processes affect soil salinity either negatively or positively, if used in nonscientific ways that lead to soil degradation, salinization, and low productivity, and thus the loss of this vital resource that we need constantly. In this research, these aforementioned factors were studied in detail and the extent of their impact on the salinity of the soil in Al-Qadisiyah, as it became clear that there are a group of human factors that led to the emergence of the problem of salinity within the soil of Al-Qadisiyah sub-district, and that this phenomenon is expanding at the expense of arable land.